Spatio-temporal characteristics of malaria transmission in Loreto region between 2000 and 2019 - Casanova Rojas de Casapia, Wilma Selva (2022)
Introduction: The elimination of malaria is the definitive solution to prevent the growing resistance to drugs and insecticides from threatening the progress made since the beginning of the 21st century. Objective: To analyze the spatio-temporal characteristics of malaria transmission in the Loreto region. Methods: We carried out a time series study, and the weekly incidence of malaria in Loreto in the last 20 years (2000-2019) was analyzed using data from the Epidemiological Surveillance System of the Ministry of Health. With this information, we modeled the weekly incidence of malaria across the Loreto surveillance reporting units and determine its spatio-temporal characteristics at the macro and micro-regional levels. Additionally, we characterized the “hot zones” and their stability over time. Results: During the last 20 years, we observed that Loreto has a seasonal malaria transmission, of moderate intensity, with different areas of diffuse transmission, Additionally, we observed that the three “hottest” health networks were, consistently, Maynas Ciudad, Loreto, and Datem del Marañón, with each of them also exhibiting different microregional hot zones of high temporal stability during its seasonal ups and downs. Conclusions: Loreto is a receptive region for malaria whose transmission is characterized by a seasonal pattern, of moderate intensity, with areas of diffuse transmission and the presence of active foci of high transmission (macro and micro-regional hot zones) with high temporal stability.